Growth performance of four potential species for planting stock using stem cutting propagation - Majin, Nur Nadzrin (2017)
Vegetation affects surfical and mass stability of slopes in significant ways. Therefore, soil bioengineering practices utilizes plant parts to overcome soil erosion and slope stabilization problem through right planting techniques coupled with right choices of plant species. Numerous literatures by scholars and proven application can be seen worldwide, but research and application of soil bioengineering practices still far from sufficient in our country. The aim of this research is to quantify growth performance including survival rate, rooting ability and effect of treatment of four different plant species planted in soil according to live-fascine technique. A full factorial experimental design involving eight treatments (2 types of wound * 2 position of wound * 2 hormone treatment) and one control were perform on each species with four replications of each treatment. Main variables examined including species (Leucaena leucocephala, Gliricidia sepium, Lagerstroemia indica and Baphia nitida), types of wound (slice and incision), position of wound (nodes and internodes) and application of hormone (with or without hormone). Following treatment, the cuttings were individually planted 5 cm deep in the soil in a prepared planting box. Evaluation and extraction of cuttings was made after five months planting duration. The registered survived cuttings after five months from installation were vary between species where Leucaena leucocephala as the highest with 72%, followed by Baphia nitida, Gliricidia sepium and Lagerstroemia indica at 47%, 31% and 22% respectively. Observed rooting performance had revealed ability of all the species tested to root from cuttings where after five months planted, some individuals roots recorded length more than two meters long. Baphia nitida showed highest rooting rate at 37% followed by Leucaena leucocephala (26%), Gliricidia sepium (20%) and Lagerstroemia indica (17%). Baphia nitida and Lagerstroemia indica had showed higher rooting rate than Leucaena leucocephala and Gliricidia sepium where all the survived cuttings were rooted. The effect of species was highly significant for all shoot and root properties. Mean separation by Duncan Multiple Range Test revealed Gliricidia sepium have significantly higher in shoot length, shoot diameter, root length and root diameter; while Baphia nitida have significantly higher in root number compare to the other species. Based on the treatments combination applied on all cuttings, incision wounding gave higher mean value of shoot and root properties compare to slice wounding. Regardless of type of wound, wounding at nodes also showed higher mean value of shoot and root properties as compared to wounding at internodes. In addition, great variation showed by cuttings with regards to hormone treatment where contrary result between treated and untreated cuttings at nodes and also at internodes for both type of wound. There are no significant difference were found between other treatments alone. However, some interaction between treatments had showed significant effect such as three-way interaction between species, type of wound and position of wound where Baphia nitida with incision at internodes has the highest mean value of shoot number. Interaction between position of wound and hormone treatment also showed significant effect for shoot length. Surprisingly, wounding at nodes without hormone application give the highest mean value. Significant effect for root number were found at two interaction; between species and types of wound where highest mean value of root number showed by Baphia nitida cuttings with slice wounding, and for interaction between type of wound and position of wound highest mean value of root number was showed by incision wounding at internodes. The result suggest that the four species tested showed well growth when planted via stem cutting. Treatment applied also give significant effect even though each treatment alone did not influence shoot and root formation directly. Enhancement on treatment combination may lead to fruitful method for planting stock not only for the species studied but also in selection of new species for vegetative propagation through stem cuttings.